2024
DOI: 10.1021/acs.chemrev.3c00532
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions and Dynamics in Mixed Three- and Low-Dimensional Lead Halide Perovskites

Mantas Simenas,
Anna Gagor,
Juras Banys
et al.

Abstract: Lead halide perovskites are extensively investigated as efficient solutionprocessable materials for photovoltaic applications. The greatest stability and performance of these compounds are achieved by mixing different ions at all three sites of the APbX 3 structure. Despite the extensive use of mixed lead halide perovskites in photovoltaic devices, a detailed and systematic understanding of the mixing-induced effects on the structural and dynamic aspects of these materials is still lacking. The goal of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 442 publications
2
10
0
Order By: Relevance
“…This behavior is interpreted as a dielectric signature of a phase transition between the LT and HT phases in AGAPbI 3 , as these temperature conditions closely align with the phase transition temperature determined from our calorimetric measurements upon heating (400 K). Moreover, a sudden increase of ε′ has been reported for many hybrid perovskites when crystal structures changed from ordered architectures with frozen molecular motions to disordered ones with rotated organic cations. Dielectric behavior of AGAPbI 3 is therefore consistent with unlocking of AGA + rotations in the HT phase. The second dielectric anomaly is evident solely in the dielectric permittivity spectra of the LT phase for probe frequencies ranging from 1 × 10 0 to 1 × 10 6 Hz.…”
Section: Resultsmentioning
confidence: 87%
“…This behavior is interpreted as a dielectric signature of a phase transition between the LT and HT phases in AGAPbI 3 , as these temperature conditions closely align with the phase transition temperature determined from our calorimetric measurements upon heating (400 K). Moreover, a sudden increase of ε′ has been reported for many hybrid perovskites when crystal structures changed from ordered architectures with frozen molecular motions to disordered ones with rotated organic cations. Dielectric behavior of AGAPbI 3 is therefore consistent with unlocking of AGA + rotations in the HT phase. The second dielectric anomaly is evident solely in the dielectric permittivity spectra of the LT phase for probe frequencies ranging from 1 × 10 0 to 1 × 10 6 Hz.…”
Section: Resultsmentioning
confidence: 87%
“…Hybrid organic–inorganic lead halides have attracted enormous interest in recent years. One of the most studied subgroup are three-dimensional (3D) perovskites of APbX 3 stoichiometry, where A denotes a small organic cation (methylammonium, MA; formamidinium, FA; methylhydrazinium, MHy; aziridinium, AZR) and B stands for halogen (Cl, Br, I). These compounds exhibit wide range of functional properties, including photovoltaic, photoluminescence (PL), and excellent multiphoton absorption. They are, therefore, placed as strong candidates for new generation solar cells, light-emitting diodes (LEDs), and photodetectors . MHy-based analogues are exceptional in this category since they crystallize in the polar crystal structures and manifest the Second-Harmonic Generation (SHG), benefiting from the lack of the inversion center. An important feature of MHy + is also its high dielectric permittivity and dipole moment. , It was demonstrated that these properties make MHyPbCl 3 attractive optical switch while MHyPbBr 3 exhibits switchable dielectric properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the 3D perovskites are rare and can be formed for a few small organic cations only, such as methylammonium (MA + ), formamidinium (FA + ), aziridinium (AZR + ), and methylhydrazinium (MHy + ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. One of the methods to enhance the diversity and modify the properties of these 3D lead halide perovskites is the preparation of mixed systems [ 10 , 11 ]. A more efficient way is, however, the employment of larger organic cations, which allow the synthesis of various lower-dimensional structures [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome problems with the large exciton binding energy of single-layered 2D perovskites, quasi-layered perovskites comprising two different cations can be synthesized. Most famous are Dion–Jacobson (DJ) (A′A n−1 Pb n X 3n+1 ) and Ruddlesden–Popper (RP) (A″ 2 A n−1 Pb n X 3n+1 ) compounds (n indicates the number of octahedral layers within each inorganic slab), in which small cage cations A are located in the voids of inorganic slabs and large divalent (A′) or monovalent (A″) cations separate the slabs [ 11 , 18 , 21 ]. It is worth adding that in such systems, an increase in the inorganic slab thickness (number of layers, n) improves photovoltaic properties [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation